Tristan Corbire and the Poetics of Irony. - Lunn-Rockliffe, Katherine (Oxford modern languages and literature monographs., 2006)
This is a study of the 19th-century French poet, Tristan Corbi--egrave--;re. Using close textual readings from Les Amours jaunes, the only collection published in Corbi--egrave--;re's lifetime, it examines his self-contradictory style. Corbi--egrave--;re's use of irony is shown to be a means of exploring the doubts of modern man and the spiritual void of commodity culture. - ;Tristan Corbi--egrave--;re is often viewed as the archetypal po--egrave--;te maudit, a misunderstood rebel and bohemian prankster. This is a study of the poet's innovative use of language. It uses the critical tool of iro.